Fuel cell fundamentals - O'Hayre, Ryan P. (Hoboken, N.J. Wiley & Sons, 2009)
As the search for alternative energy technologies heats up, no topic is hotter than fuel cells. Updating its successful first edition, Fuel Cell Fundamentals, Second Edition gives advanced undergraduate and beginning level graduate students an important introduction to the basic science and engineering behind fuel cell technology. Emphasizing the foundational scientific principles that apply to any fuel cell type or technology, the text provides straightforward descriptions of how fuel cells work, why they offer the potential for high efficiency, and how their unique advantages can best be used.
Fuel cell thermodynamics -- Fuel cell reaction kinetics -- Fuel cell charge transport -- Fuel cell mass transport -- Fuel cell modeling -- Fuel cell characterization -- Overview of fuel cell types -- PEMFC and SOFC materials -- Overview of fuel cell systems -- Fuel processing subsystem design -- Thermal management subsystem design -- Fuel cell system design -- Environmental impact of fuel cells
Keywords: Fuel cells -- Textbooks